1977
DOI: 10.1136/hrt.39.8.829
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of myocardial metabolism in coronary arterial disease by beta-blockade.

Abstract: Twenty patients with angina pectoris associated with obstructive coronary arterial disease were investigated by stressing the heart by atrial pacing. Arterial and coronary sinus blood was sampled and the time taken to provoke angina (pacing time) measured. Nine of the patients acted as a control group and did not receive beta-blocking drugs. In this group both pacing time and myocardial lactate extraction were reproducible provided that 45 minutes rest was allowed between pacing tests: we have called this peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
1

Year Published

1978
1978
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 13 publications
1
20
1
1
Order By: Relevance
“…In contrast, no primary effect of propranolol on the oxygen consumption of normal isolated myocardium is apparent in these data. Thus, although it has been postulated that fl-adrenoceptor blockade has an effect on myocardial metabolism that is independent of its effect on either cardiac autonomic nervous control (53) or hemodynamic variables (67,68), no support for these concepts is found either in these data or in other recent data (69) derived in a somewhat less direct manner.…”
Section: F-adrenoceptor Assayscontrasting
confidence: 50%
“…In contrast, no primary effect of propranolol on the oxygen consumption of normal isolated myocardium is apparent in these data. Thus, although it has been postulated that fl-adrenoceptor blockade has an effect on myocardial metabolism that is independent of its effect on either cardiac autonomic nervous control (53) or hemodynamic variables (67,68), no support for these concepts is found either in these data or in other recent data (69) derived in a somewhat less direct manner.…”
Section: F-adrenoceptor Assayscontrasting
confidence: 50%
“…We have recently shown that beta-blockers have a similar beneficial effect (Jackson et al, 1977). Of 19 patients with abnormal lactate metabolism, 15 responded to glyceryl trinitrate and 16 to propranolol.…”
Section: Discussionmentioning
confidence: 96%
“…This finding may have a significant impact in light of evidence that intravenous therapy alone may be difficult to titrate; 35% of patients treated with intravenous atenolol, in the study by Mangano et al [1], had intraoperative tachycardia. In addition, the beneficial effects of b-blockade are multifactorial; even if they are administered in submaximal doses, b-blockade may cause reductions of myocardial metabolism, oxygen demand, shear stress, inflammatory responses, platelet aggregability, and plaque disruption [17,23,37,38]. Additional data are needed to determine which degree of blockade is required to achieve these beneficial effects.…”
Section: Discussionmentioning
confidence: 99%